2012
DOI: 10.1002/jmv.23412
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between beta‐herpesviruses reactivation and development of complications after autologous peripheral blood stem cell transplantation

Abstract: The relationship between beta-herpesviruses reactivation and the development of complications after autologous peripheral blood stem cell transplantation was investigated. Viral genomic sequences were detected by the polymerase chain reaction, virus-specific antibodies by ELISA, and human herpesvirus (HHV)-6 variants by restriction endonuclease analysis. Virus reactivation, serum levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, soluble IL-2 receptor (sIL-2R), IL-2, and IL-4 were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
0
14
1
Order By: Relevance
“…Human pathogens include varicella-zoster virus (VZV) (73), which causes chicken pox and shingles; HCMV, which causes mental retardation and deafness in neonates and retinitis in immunocompromised patients (63); human herpesvirus 6 (HHV-6), which causes roseola infantum and febrile seizures (74); Epstein-Barr virus (EBV), which causes infectious mononucleosis and is associated with cancers, including Burkitt's lymphoma (75); HHV-7, which may stimulate HCMV reactivation and tissue transplant rejection (76); and HHV-8, which causes Kaposi's sarcoma (77). More than 90% of adults have been infected with and retain a latent form of one or more of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Human pathogens include varicella-zoster virus (VZV) (73), which causes chicken pox and shingles; HCMV, which causes mental retardation and deafness in neonates and retinitis in immunocompromised patients (63); human herpesvirus 6 (HHV-6), which causes roseola infantum and febrile seizures (74); Epstein-Barr virus (EBV), which causes infectious mononucleosis and is associated with cancers, including Burkitt's lymphoma (75); HHV-7, which may stimulate HCMV reactivation and tissue transplant rejection (76); and HHV-8, which causes Kaposi's sarcoma (77). More than 90% of adults have been infected with and retain a latent form of one or more of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Available data suggest that HHV-7 infections are common after transplantation and may lead to CMV reactivation and cytomegalovirus disease (Chan et al 1997; Chapenko et al 2012; Kidd et al 2000). In the present study, HHV-7 viraemia was found mostly (94 %) before CMV infection, which suggests a possible interaction between these β-herpesviruses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reactivation of HHV-7 virus is very rarely studied and its clinical significance remains still unknown (Ljungman et al 2008). Some authors have postulated a potential increase in virulence of HHV-7 in the course of a simultaneous CMV reactivation, leading to a greater risk of CMV disease after transplantation (Chan et al 1997; Chapenko et al 2012; Zawilińska et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…HHV-6B is the dominant virus present in the peripheral blood mononuclear cells (PBMCs) of healthy adults, at least in industrialized countries, and is also the virus that reactivates in a significant majority of both solid organ and stem cell transplant cases in these countries [21, 28, 45, 53, 57, 65, 74, 100, 108, 128], while both HHV-6A and HHV-6B are detected with similar frequency in the plasma of bone marrow transplant patients [97, 114]. HHV-6B is also frequently detected in the GI tract of solid organ transplant patients [76], has been identified in endodontic abscesses [54], and is the virus found in adenoids and tonsils, particularly in children affected by upper airway infections [35].…”
Section: Distinct Epidemiology and Disease Associationsmentioning
confidence: 99%
“…In addition, although an overwhelming majority of post-transplant reactivation occurs with HHV-6B [28, 29, 53], HHV-6A DNA and mRNA are found more frequently than HHV-6B in patients with neuroinflammatory diseases such as multiple sclerosis (MS) [9, 14, 48, 115] and rhomboencephalitis [37]. HHV-6A has been found predominantly in the CNS of a subset of patients with MS, and active HHV-6A infection has been detected in blood [8, 9, 11] and in CSF [110] of patients with relapsing/remitting MS [810, 14, 20, 110, 115, 131].…”
Section: Distinct Epidemiology and Disease Associationsmentioning
confidence: 99%